DAMPAK BELANJA NEGARA TERHADAP TINGKAT KEGIATAN EKONOMI DI INDONESIA - Christine Tambunan; Jakaria Amin (Media Ekonomi, 2019)
This study is to examine and to analyze the impact of State Budget Expenditure on the Level of Economic Activity in Indonesia. Using the Autoregressive-Distributed Lag (ARDL) method. And using data from 2008-2017. The result of this empirical study is that in the long run, state budget expenditure, consisting of Employee Expenditure, Special Allocation Fund (DAK) and General Allocation Fund (DAU,) has a significant positive effect on Level of Economic Activity. On the contrary, Capital Expenditure has a significant negative impact on growth. While Goods Expenditure shows a negative effect, though it was not statistically significant.